Mind the Screen Media Concepts According to Thomas Elsaesser - Kooijman, Jaap; Pisters, Patricia; Strauven, Wanda (Amsterdam University Press, 2008)
Mind the Screen pays tribute to Thomas Elsaesser, a pioneering and leading scholar in the field of film and media studies. The contributions present a close-up of media concepts developed by Elsaesser, providing a mirror for all types of audiovisual screens, from archaeological pre-cinematic screens to the silver screen, from the TV set to the video installation and the digital e-screen, and from the city screen to the mobile phone display. The book is divided into three 'Acts': Melodrama, Memory, Mind Game; Europe-Hollywood-Europe; and Archaeology, Avant-Garde, Archive. This title is available in the OAPEN Library - http://www.oapen.org.